Investigation of the role of RACKI in T lymphocyte migration - Rudolph, Christine (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2012)
Induction of the innmune response and production of pro-inflammatory cytokines results in the upregulation of ICAM-1 expressed on endothelial cells. Binding of ICAM-1 to the β2 integrin receptor LFA-1 on T cells induces T cell polarisation allowing the cell to migrate between endothelial cells to the site of injury or inflammation. Transendothelial migration involves the rearrangement of the cellular cytoskeleton, a process dependent on translocation of Protein Kinase C (PKC) isotypes. Receptor for Activated C Kinase 1 (RACK1) is a scaffolding protein which directs the subcellular localisation and activity of PKC, where it phosphorylates specific substrates in response to different stimuli. RACK1 has been shown to interact with membrane- bound receptors, including the cytoplasmic domain of (3 integrin, thus linking PKC to integrin- mediated signal transduction and implicating a role for RACK1 in integrin-mediated immune cell adhesion and migration. Recent studies on RACK1 suggest that this adaptor protein plays an essential role in migratory capacity in all cell types where it is expressed. Despite its apparent dominant role in cell migration, the role of RACK1 in the context of immune cell migration has been widely overlooked. This thesis aimed to characterise RACK1 and any potential regulatory function in integrin-mediated immune cell migration. To investigate the function of RACK1 in mediating immune cell migration, four projects have been pursued.
Keywords: Molecular Medicine, Ph.D.; Ph.D. Trinity College Dublin